2020
DOI: 10.1002/jmv.26007
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged SARS‐CoV‐2 RNA detection in anal/rectal swabs and stool specimens in COVID‐19 patients after negative conversion in nasopharyngeal RT‐PCR test

Abstract: Coronavirus disease 2019 (COVID-19) is a rapidly escalating pandemic that has spread to many parts of the world. Current data available on COVID-19 would suggest that SARS-CoV-2 virus is shed through the gastrointestinal system via feces. Some reports further indicate that a subset of COVID-19 patients may continue to have positive SARS-CoV-2 anal/rectal swab and stool test after negative conversion of nasopharyngeal test. This paper analyses current literature to so as to shed some light on this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 19 publications
3
65
0
4
Order By: Relevance
“…In addition, oral sex and anal sex preferences decreased during the COVID-19 outbreak. Previously, SARS-CoV-2 has been shown to be positive in rectal and anal swab samples [28,29]. The possibility of contamination between body fluids has been effective in participants' oral and anal sex preferences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oral sex and anal sex preferences decreased during the COVID-19 outbreak. Previously, SARS-CoV-2 has been shown to be positive in rectal and anal swab samples [28,29]. The possibility of contamination between body fluids has been effective in participants' oral and anal sex preferences.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with COVID‐19 need to meet criteria of recovery before hospital discharge 1 : (a) normal temperature for more than 3 days, (b) no respiratory symptoms, (c) substantially improved acute exudative lesions on chest computed tomography images, (d) two consecutively reverse transcription‐polymerase chain reaction (RT‐PCR) tests negative for SARS‐CoV‐2 RNA more than 24 hours. However, the recovered (discharged) COVID‐19 patients with retest positive for SARS‐CoV‐2 RNA have recently been reported 1‐9 . Specifically, A new report on 25 February 2020 indicated that 14% of discharged patients were tested positive for SARS‐CoV‐2 RNA in Guangdong province.…”
mentioning
confidence: 99%
“…6 In addition, viral RNA, although not equivalent to transmissible intact viral particles, has been found in patients' stool, and angiotensinconverting enzyme II receptor used by the virus to enter human cells, is widely expressed in the intestinal tract, making lower GI endoscopy a procedure of uncertain risk status. 7,8 Furthermore, infected HCPs may transmit the infection to their colleagues, patients, families, and communities, as shown by reports of hospital-based epidemics in European countries. 9 Infection prevention and control have been shown to be dramatically effective in assuring the safety of both HCPs and patients.…”
mentioning
confidence: 99%